Physical activity and menopausal symptoms in women who have received menopause-inducing cancer treatments: results from the Women's Wellness After Cancer Program. Issue 2 (February 2021) - Bailey, Tom G.; Mielke, Gregore I.; Skinner, Tina S.; Anderson, Debra; Porter-Steele, Janine; Balaam, Sarah; Young, Leonie; McCarthy, Alexandra L.
Abstract: Objective: This randomized controlled trial tested a digitally-delivered whole-of-lifestyle program for women previously treated for cancer. We investigated (1) associations between self-reported physical activity (PA) and menopausal symptoms and (2) if the intervention was associated with beneficial changes in PA and menopausal symptoms. Methods: Women were randomized to intervention ( n  = 142) or control ( n  = 138). The intervention targeted lifestyle behavior including PA. Self-reported PA (International Physical Activity Questionnaire – Short Form) and menopausal symptom (Green Climacteric Scale, GCS) data were collected at baseline, with measures repeated at 12 weeks (end of intervention) and 24 weeks (to assess sustainability). Generalized estimating equation models explored associations between PA and GCS scores. Mixed-effects generalized equation models analyzed changes within and between groups in PA and GCS scores. Results: Total GCS scores were 1.83 (95% CI: 0.11-3.55) and 2.72 (95% CI: 1.12-4.33) points lower in women with medium and high levels of PA, respectively, than in women with low levels of PA. Total average GCS scores were 1.02 (0.21-2.26) and 1.61 (0.34-2.87) points lower in those undertaking moderate or vigorous intensity PA, respectively. Time spent walking, and performing moderate and vigorous PA were not different between intervention and control. The average GCS decrease of 0.66 points (95% CI: 0.03-1.29; p time  = 0.03) over 24 weeks was not different between groups. Conclusion: This exploratory study established a stepwise association between moderate and vigorous PA and a lower total menopausal symptom score. The intervention did not appear to increase self-reported PA in women treated for early stage breast, reproductive, and blood cancers.